2023
DOI: 10.3390/plants12040796
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Precursors on Content of Polyphenols in Camellia sinensis In Vitro Callus Culture

Abstract: Plant tissue cultures are considered as potential producers of biologically active plant metabolites, which include various phenolic compounds that can be used to maintain human health. Moreover, in most cases, their accumulation is lower than in the original explants, which requires the search for factors and influences for the intensification of this process. In this case, it is very promising to use the precursors of their biosynthesis as potential “regulators” of the various metabolites’ formation. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…They are precursors of a variety of metabolites that regulate plant growth, metabolism, and interactions with environmental stimuli, such as biotic and abiotic stresses [14][15][16][17][18][19]. They have also been utilized in food supplements, pharmaceuticals, and cosmetics, and have numerous advantages for human well-being [20,21]. Chickpea seeds and sprouts contain diverse phenylpropanoids that contribute to their immense antioxidant, estrogenic, and antiproliferative activities [22].…”
Section: Introductionmentioning
confidence: 99%
“…They are precursors of a variety of metabolites that regulate plant growth, metabolism, and interactions with environmental stimuli, such as biotic and abiotic stresses [14][15][16][17][18][19]. They have also been utilized in food supplements, pharmaceuticals, and cosmetics, and have numerous advantages for human well-being [20,21]. Chickpea seeds and sprouts contain diverse phenylpropanoids that contribute to their immense antioxidant, estrogenic, and antiproliferative activities [22].…”
Section: Introductionmentioning
confidence: 99%
“…Different precursors were added to increase the accumulation of secondary metabolites. The research revealed the presence of polyphenolic compounds from the group of phenylpropanoids, flavans, and proanthocyanidins and confirmed that the addition of precursors such as phenylalanine significantly increased the accumulation of the compounds (Aksenova et al 2023 ).…”
Section: Discussionmentioning
confidence: 73%
“…A large number of publications are based on research on the polyphenol profile of extracts from different types of in vitro cultures. The authors focus on the qualitative and quantitative determination of polyphenols, also examining antioxidant potential (Aksenova et al 2023 ; Zheleznichenko et al 2023 ; Kwiecień et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%